Activity, Cloning, and Expression of an Isoamylase-Type Starch-Debranching Enzyme from Banana Fruit - Dettmann Bierhals, J.; Lajolo, F.M.; Cordenunsi, B.R.; Oliveira Do Nascimento, J.R.
Unripe bananas have a high content of starch (almost 20
Keywords: BANANA; FRUIT RIPENING; ISOAMYLASE; STARCH; STARCH-DEBRANCHING ENZYME